Emergence of intratreatment resistance to oseltamivir in pandemic influenza A H1N1 2009 virus - Valinotto, Laura Elena (2010)
Background: Pandemic influenza A H1N1 2009 virus presents a new challenge to health authorities and communities worldwide. In Argentina, the outbreak was at its peak by the end of June 2009, during the southern winter. A systematic analysis of samples from patients with pandemic H1N1 2009 studied in our laboratory (Virology Laboratory, Hospital de Niños R Gutiérrez, Buenos Aires, Argentina) detected two patients presenting intratreatment emergence of the H275Y neuraminidase mutation, which confers resistance to oseltamivir. Methods: Complementary DNAs, including the 275 codon, were obtained by reverse transcriptase PCR using viral RNAs extracted from nasopharyngeal or tracheal aspirates. Conventional sequencing and pyrosequencing were performed on each sample. In order to measure the virus susceptibility to oseltamivir, 50% inhibitory concentration determinations were performed by chemiluminescence. Results: Sequential samples of two paediatric patients under oseltamivir treatment were analysed. Pretreatment samples were composed of 100% oseltamivir-sensitive variants. In case 1, the oseltamivir-resistant variant was found 8 days after the beginning of treatment. In case 2, the viral population became resistant on the second day of treatment, with 83% of the viral population bearing the mutation and this reached 100% on the seventh day. Conclusions: We describe the intratreatment emergence of oseltamivir resistance in two paediatric patients. Pyrosequencing allowed us to detect variant mixtures, showing the transition of the viral population from sensitive to resistant.